A yttrium-aluminum oxide continuous ceramic fiber and a method of making the same

CN118908697BActive Publication Date: 2026-10-16INST OF CHEM CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310507804.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-08
Publication Date
2026-10-16
Estimated Expiration
2043-05-08

AI Technical Summary

Technical Problem

[0002]二十世纪六十年代,以SiC纤维为代表的非氧化物陶瓷纤维的商业化应用,对推动陶瓷基复合材料的发展起到了关键作用,然而非氧化物陶瓷纤维受到高温下氧化问题的影响,限制了其在特定环境中的应用

Benefits of technology

[0040] 1) The method for preparing yttrium aluminum oxide continuous ceramic fibers provided by the present invention uses melt spinning to form fibers, which is simple, environmentally friendly, and easy to scale up for production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118908697B_ABST
    Figure CN118908697B_ABST
Patent Text Reader

Abstract

This invention discloses a continuous yttrium aluminum oxide ceramic fiber and its preparation method. The continuous yttrium aluminum oxide ceramic fiber is composed of Al₂O₃ and Y₂O₃, with a molar ratio of Al to Y of 5:3.5-0.5. The crystal phase composition of the continuous yttrium aluminum oxide ceramic fiber is: pure YAG(Y₃Al₅O₃). 12 The yttrium aluminum oxide continuous ceramic fiber is a mixture of the YAG phase or Y-Al2O3 phase with at least one of the α-Al2O3, γ-Al2O3, and YAM (Y4Al2O9) phases. The average diameter of the fiber is 5-15 μm, and the tensile strength can reach up to 1.5 GPa. This invention uses melt spinning to form the fiber, which is simple, environmentally friendly, and easy to scale up for production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of composite fiber materials technology, and relates to a yttrium aluminum oxide continuous ceramic fiber and its preparation method. Background Technology

[0002] In the 1960s, the commercial application of non-oxide ceramic fibers, represented by SiC fibers, played a crucial role in promoting the development of ceramic matrix composites. However, the oxidation problem at high temperatures limited the application of non-oxide ceramic fibers in specific environments. Oxide ceramic fibers, due to their excellent oxidation resistance, can be used in high-temperature aerobic environments, and also possess good flexibility, allowing them to be woven and used as structural reinforcement materials in ceramic matrix composites. Oxide short fibers were initially produced and used as refractory and heat-insulating materials, while the later-developed SiO2-containing continuous Al2O3 fibers can be used as reinforcement materials for lightweight alloys. Oxide continuous ceramic fibers are widely used in aerospace, military, automotive, and other fields due to their high strength, high modulus, and excellent oxidation resistance. Their excellent mechanical properties mainly depend on their dense nanocrystalline structure. Numerous studies have shown that the tensile strength of oxide continuous ceramic fibers decreases at high temperatures due to the increase in grain size. Therefore, selecting oxide components with good high-temperature stability and refining the grain size of the fibers are crucial for the preparation of high-performance oxide continuous ceramic fibers.

[0003] Yttrium aluminum garnet (YAG) fiber is a novel inorganic ceramic fiber developed in the 1990s. YAG is the only binary compound in the Y₂O₃-Al₂O₃ system that can exist stably at high temperatures (chemical formula Y₃Al₅O). 12 It belongs to the cubic crystal system, has a garnet structure, a melting point of 1942℃, and a density of 4.55 g / cm³. 3 With its isotropic properties, good chemical stability, excellent high-temperature creep resistance, and good resistance to water vapor corrosion, fiberization of YAG is an effective way to realize its application in lightweight, high-temperature resistant thermal protection materials and structural reinforcement materials. Compared with other oxide ceramic fibers, YAG fibers have better creep resistance, which is an order of magnitude higher than that of alumina fibers. Therefore, YAG fibers are a very promising reinforcement material that can be used in high-temperature oxygen-containing environments.

[0004] Currently, there are two main methods for preparing YAG fibers: the melt method and the sol-gel method. The melt method is mostly used to prepare single-crystal YAG fibers. This process requires high temperatures, generally above 1500℃. Due to its high energy consumption, high cost, and complex preparation process, its further development is limited. The sol-gel method is mostly used to prepare polycrystalline YAG fibers. Because this method is simple, has mild and controllable reaction conditions, it is the commonly used method for preparing YAG fibers reported in the literature.

[0005] Patent CN106927808 B uses AI 13 Using alumina sol, γ-AlOOH nanoparticle dispersion, and yttrium oxide sol as raw materials, a spinning aid is added to an acidic solution. Continuous gel fiber precursors with lengths up to 3 kilometers are prepared by dry spinning, followed by heat treatment to obtain yttrium aluminum garnet long fibers with diameters of 6-12 μm. This method combines the advantages of slurry and sol-gel methods for preparing oxide fibers, producing fiber monofilaments with a tensile strength close to 1.0 GPa. However, the presence of chloride (Cl) in the spinning raw materials and the addition of spinning aids are detrimental to the preparation of environmentally friendly and high-performance fibers. Furthermore, the presence of γ-AlOOH nanoparticles in the spinning raw materials easily leads to phase separation between the nanoparticles and the bulk oxide during sintering, hindering densification. Sintering at high temperatures is necessary, but high-temperature sintering increases grain size, thus affecting the fiber's mechanical properties.

[0006] Patent CN 111978550 A describes a method for preparing yttrium aluminum garnet (YAG) long fibers using organic polymer precursors. These fibers exhibit high purity and flexibility. Although no spinning aids are used, the preparation process involves raw materials containing chlorine, such as aluminum chloride and yttrium chloride. During synthesis and subsequent sintering, acidic substances like HCl are generated, which can negatively impact the environment and equipment. Furthermore, the excessive use of organic solvents in dissolution, extraction, filtration, and concentration processes inevitably leads to large amounts of organic solvent waste during industrial-scale production. Additionally, the YAG fibers prepared by this method have a relatively large diameter, which is unfavorable for producing high-strength YAG long fibers. Summary of the Invention

[0007] The purpose of this invention is to provide a continuous ceramic fiber of yttrium aluminum oxide and its preparation method.

[0008] The yttrium aluminum oxide continuous ceramic fiber provided by this invention is composed of Al2O3 and Y2O3, wherein the molar ratio of Al to Y elements in the fiber is 5:3.5-0.5; specifically, it can be 5:3.5, 5:3, 5:2, 5:1, or 5:0.5.

[0009] The crystal phase composition of the yttrium aluminum oxide continuous ceramic fiber is: pure YAG(Y3Al5O) 12 A mixture of α-Al2O3, γ-Al2O3 and YAM(Y4Al2O9) phases or YAG phases;

[0010] The yttrium aluminum oxide continuous ceramic fiber has an average diameter of 5-15 μm, specifically 10 μm, and a tensile strength of up to 1.5 GPa.

[0011] The yttrium aluminum oxide continuous ceramic fibers of this invention are prepared by polymer melt spinning, a process that is environmentally friendly; the resulting yttrium aluminum oxide continuous ceramic fibers are composed of pure YAG(Y3Al5O3) 12 ) phase or YAG phase with α-Al2O3, γ-Al2O3, YAG(Y3Al5O) 12 It is a mixture of at least one of the phases YAM (Y4Al2O9) and YAM (Y4Al2O9), and the proportions are adjustable when mixing multiple phases.

[0012] The method for preparing yttrium aluminum oxide continuous ceramic fibers provided by the present invention includes:

[0013] 1) The yttrium aluminum oxide ceramic precursor is melt-spun to obtain fiber filaments;

[0014] 2) The fiber filaments are subjected to steam crosslinking and degumming treatment or high-temperature steam crosslinking and degumming integrated treatment to obtain inorganic fibers;

[0015] 3) The inorganic fibers are subjected to ceramicization treatment to obtain the yttrium aluminum oxide continuous ceramic fibers.

[0016] In step 1) of the above method, the softening point of the yttrium aluminum oxide ceramic precursor in the melt spinning step is 110-180℃; specifically, it can be 120℃.

[0017] The yttrium aluminum oxide ceramic precursor was prepared by the following method:

[0018] An aluminum source and a yttrium source are added to a solvent and stirred and refluxed at a heating temperature of 60-110℃ for 0.5-3 hours. A complexing agent is added at a heating temperature of 60-90℃ and refluxed for 0.5-2 hours. A mixture of water and n-propanol with a mass ratio of 1:4 is then added dropwise at a dropping rate of 1 drop / s, and refluxed for 2 hours after the addition is complete. The mixture is then distilled at a heating temperature of 180-270℃ (specifically 260℃) for 0.5-6 hours, held at that temperature for 2 hours, and then cooled to room temperature to obtain a yttrium aluminum oxide ceramic precursor.

[0019] The amounts of aluminum source and yttrium source used, converted to the molar ratio of Al and Y elements, are 5:3.5-0.5; specifically, they can be 5:3.5-1, 5:1-0.5, 5:3.5, 5:3, 5:2, 5:1 or 5:0.5.

[0020] The aluminum source is aluminum isopropoxide;

[0021] The yttrium source is yttrium acetylacetone;

[0022] The solvent is n-propanol;

[0023] The complexing agent is acetylacetone;

[0024] The acetylacetone was 0.6 times the total molar fraction of aluminum isopropoxide and yttrium acetylacetone;

[0025] The molar ratio of total aluminum source, yttrium source, and water is 1:0.6;

[0026] The melt spinning temperature is 20-60°C higher than the softening point of the precursor; specifically, it can be 45°C.

[0027] In the melt spinning process, the diameter of the exit hole is 0.1-1 mm; specifically, 0.2 mm.

[0028] The screw extrusion pressure is 5-30 MPa; specifically, it can be 20 MPa.

[0029] The winding frequency is 15-40Hz; specifically 35Hz.

[0030] In step 2) of the above method, when the molar ratio of Al and Y elements used to prepare the yttrium aluminum oxide ceramic precursor is less than 5:1, such as 5:3.5-1 (excluding endpoint 1), the fiber filament is subjected to high-temperature steam crosslinking and debinding integrated treatment to obtain inorganic fiber.

[0031] The operation of the high-temperature steam crosslinking and debinding integrated treatment is as follows: the fiber filament is placed in a honeycomb-type steam furnace, and water vapor is continuously introduced during the debinding and sintering process. The steam intake is 80-200L / h (200L / h is not acceptable, such as 80-120L / h or 80L / h). The temperature is raised to 600℃ at a heating rate of 0.5-2℃ / min (such as 0.5℃ / min), and held at the target temperature of 600℃ for 1 hour. The steam intake is then turned off, and the temperature is then lowered to room temperature.

[0032] In step 2) of the above method, when the molar ratio of Al and Y elements used to prepare the yttrium aluminum oxide ceramic precursor is greater than or equal to 5:1, such as 5:1-0.5, the fiber precursor can be subjected to steam crosslinking and debinding treatment, or the high-temperature steam crosslinking and debinding integrated treatment can be performed to obtain inorganic fiber. Preferably, the steam crosslinking and debinding treatment is performed.

[0033] The steam crosslinking and debinding process is as follows: the fiber filaments are placed in a constant temperature and humidity chamber, heated to 75-90℃ (e.g., 85℃), and kept at a relative humidity of 75-95% (e.g., 80%) for 0-60 minutes (e.g., 0, 20, 40, 60 minutes). After cooling to room temperature, the fiber after steam crosslinking is placed in a debinding and sintering integrated furnace to debind and prepare inorganic fiber. The temperature is increased to 600℃ at a rate of 1℃ / min, and kept at the target temperature of 600℃ for 1 hour before being cooled to room temperature.

[0034] In step 3) of the above method, the rate of temperature increase from room temperature to ceramization temperature is 10-30℃ / min; specifically, 10℃ / min.

[0035] The ceramization temperature is 1100-1500℃; specifically 1200℃.

[0036] The ceramization time is 30 minutes to 2 hours; specifically, 1 hour.

[0037] The atmosphere for ceramicization is air.

[0038] Furthermore, the yttrium aluminum oxide continuous ceramic fiber prepared by the above method and its application in the preparation of materials with at least one of the properties of structural reinforcement and high-temperature insulation are also within the scope of protection of this invention.

[0039] The present invention has the following beneficial effects:

[0040] 1) The method for preparing yttrium aluminum oxide continuous ceramic fibers provided by the present invention uses melt spinning to form fibers, which is simple, environmentally friendly, and easy to scale up for production.

[0041] 2) The crystal structure of the yttrium aluminum oxide continuous ceramic fiber provided by this invention is pure YAG(Y3Al5O3) 12 The mixture of the YAG phase or YA phase with at least one of the α-Al2O3, γ-Al2O3 and YAM (Y4Al2O9) phases, and the proportions can be adjusted when mixing multiple phases.

[0042] 3) The yttrium aluminum oxide continuous ceramic fiber provided by the present invention has an average diameter of 5-15 μm and a tensile strength of up to 1.5 GPa. Attached Figure Description

[0043] Figure 1 These are XRD patterns of the fibers prepared at different temperatures in Example 2.

[0044] Figure 2 This is an SEM image of the fibers in Example 3.

[0045] Figure 3 These are XRD patterns of the fibers prepared at different temperatures in Example 3.

[0046] Figure 4 This is the TG diagram of the precursor in Comparative Example 1.

[0047] Figure 5 This is a SEM image of the fiber precursor in Comparative Example 2. Detailed Implementation

[0048] The present invention will now be described in further detail with reference to specific embodiments. The given embodiments are merely illustrative of the invention and not intended to limit its scope. The embodiments provided below can serve as a guide for further improvements by those skilled in the art and do not constitute a limitation on the invention in any way.

[0049] Unless otherwise specified, the experimental methods used in the following examples are conventional methods, performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Unless otherwise specified, the materials and reagents used in the following examples are commercially available.

[0050] Example 1

[0051] Preparation of Yttrium Aluminum Oxide Continuous Ceramic Fibers

[0052] 1) Precursor synthesis: Aluminum isopropoxide and yttrium acetylacetonate were added to n-propanol, with the molar ratio of aluminum isopropoxide to yttrium acetylacetonate equivalent to Al:Y elements being 5:1. The mixture was stirred and refluxed at 90°C for 3 hours. Subsequently, 0.6 molar fractions of acetylacetonate were added to aluminum isopropoxide and yttrium acetylacetonate at 80°C, and the mixture was refluxed for 1.5 hours. Then, a mixture of water and n-propanol with a mass ratio of 1:4 was added dropwise at a rate of 1 drop / s, with the molar ratio of aluminum isopropoxide, yttrium acetylacetonate, and water being 1:0.6. The mixture was refluxed for 2 hours after the addition was complete. The mixture was then distilled at atmospheric pressure at 230°C for 5 hours, held at that temperature for 2 hours, and then cooled to room temperature to obtain the yttrium aluminum oxide ceramic precursor, which had a softening point of 120°C and a ceramic yield of 36.2%.

[0053] 2) Melt spinning: A yttrium aluminum oxide ceramic precursor with a softening point of 120℃ and a molar ratio of Al to Y of 5:1 is heated to 165℃. After it melts into a uniform melt and removes residual bubbles, melt spinning is carried out at 165℃. The filament outlet diameter is 0.2mm, the screw extrusion pressure is 20MPa, and the fiber is taken in at a rate of 35Hz to obtain fiber filaments.

[0054] 3) Steam crosslinking and desizing treatment: The obtained fiber filaments were placed in a constant temperature and humidity chamber, heated to 85℃, and held at 80% relative humidity for 60 minutes, then cooled to room temperature. Subsequently, the steam-crosslinked fibers were placed in a desizing and sintering integrated furnace to desizing and prepare inorganic fibers. The temperature was increased to 600℃ at a rate of 1℃ / min, held at the target temperature of 600℃ for 1 hour, and then cooled to room temperature to obtain inorganic fibers.

[0055] 4) Ceramization: The obtained inorganic fibers are placed in an alumina fiber fast-firing furnace with air in the furnace atmosphere. The temperature is increased to 1200℃ at 10℃ / min, held for 1 hour, and then cooled to room temperature to obtain yttrium aluminum oxide continuous ceramic fibers.

[0056] The resulting fibers had an average diameter of 10 μm, an average tensile strength of 1.16 GPa, a crystal phase composition of YAG phase and α-Al2O3 phase, and an average grain size of 66.2 nm.

[0057] Example 2

[0058] Preparation of Yttrium Aluminum Oxide Continuous Ceramic Fibers

[0059] 1) Precursor synthesis: Aluminum isopropoxide and yttrium acetylacetonate were added to n-propanol, with the molar ratio of aluminum isopropoxide to yttrium acetylacetonate equivalent to Al:Y elements being 5:0.5. The mixture was stirred and refluxed at 90°C for 3 hours. Subsequently, 0.6 molar fractions of acetylacetonate were added to aluminum isopropoxide and yttrium acetylacetonate at 80°C, and the mixture was refluxed for 1.5 hours. Then, a mixture of water and n-propanol with a mass ratio of 1:4 was added dropwise at a rate of 1 drop / s, with the molar ratio of aluminum isopropoxide, yttrium acetylacetonate, and water being 1:0.6. The mixture was refluxed for 2 hours after the addition was complete. The mixture was then distilled at atmospheric pressure at 230°C for 6 hours, held at that temperature for 2 hours, and then cooled to room temperature to obtain the yttrium aluminum oxide ceramic precursor, which had a softening point of 120°C and a ceramic yield of 34.5%.

[0060] 2) Melt spinning: The yttrium aluminum oxide ceramic precursor with a softening point of 120℃ and a molar ratio of Al to Y of 5:0.5 is heated to 165℃. After it melts into a uniform melt and removes residual bubbles, melt spinning is carried out at 165℃. The filament outlet diameter is 0.2mm, the screw extrusion pressure is 20MPa, and the fiber is taken in at a rate of 35Hz to obtain fiber filaments.

[0061] 3) Steam crosslinking and debinding treatment: Same as in Example 1;

[0062] 4) Ceramization: Same as Example 1.

[0063] The resulting fibers had an average diameter of 10 μm, an average tensile strength of 1.35 GPa, a crystal phase composition of YAG phase and γ-Al2O3 phase, and an average grain size of 5.2 nm.

[0064] XRD patterns of fibers prepared at different temperatures are attached. Figure 1As shown in the figure, the fiber exhibits an amorphous crystalline phase composition at temperatures below 950℃. The γ-Al₂O₃ phase begins to appear at 1000℃. Several sharp diffraction peaks appear at 1150℃, belonging to the YAG and YAlO₃ phases. At 1250℃, the characteristic diffraction peaks of the γ-Al₂O₃ and YAlO₃ phases disappear, indicating that these two phases appear as intermediate phases, while the characteristic peaks of the α-Al₂O₃ phase begin to appear. The final crystalline phase composition of the fiber is YAG and α-Al₂O₃. With increasing temperature, the characteristic peaks of both phases gradually intensify and narrow, indicating that the grain size of both phases gradually increases and the lattice structure gradually becomes more complete.

[0065] Example 3

[0066] Preparation of Yttrium Aluminum Oxide Continuous Ceramic Fibers

[0067] 1) Precursor synthesis: Aluminum isopropoxide and yttrium acetylacetonate were added to n-propanol, with the ratio of aluminum isopropoxide to yttrium acetylacetonate being equivalent to a molar ratio of Al to Y of 5:3. The mixture was stirred and refluxed at 90°C for 3 hours. Then, 0.6 molar fractions of acetylacetonate (based on the total amount of aluminum isopropoxide and yttrium acetylacetonate) were added to acetylacetonate at 80°C, and the mixture was refluxed for 1.5 hours. A mixture of water and n-propanol (mass ratio 1:4) was then added dropwise at a rate of 1 drop / s, with the molar ratio of aluminum isopropoxide, yttrium acetylacetonate, and water being 1:0.6. The mixture was refluxed for 2 hours after the addition was complete. The mixture was then distilled at atmospheric pressure at 260°C for 4 hours, held at that temperature for 2 hours, and then cooled to room temperature to obtain the yttrium aluminum oxide ceramic precursor. The softening point was 120°C, and the ceramic yield was 38.7%.

[0068] 2) Melt spinning: A yttrium aluminum oxide ceramic precursor with a softening point of 120℃ and a molar ratio of Al to Y of 5:3 is heated to 165℃. After it melts into a uniform melt and removes residual bubbles, melt spinning is carried out at 165℃. The filament outlet diameter is 0.2mm, the screw extrusion pressure is 20MPa, and the fiber is taken in at a rate of 35Hz to obtain fiber filaments.

[0069] 3) High-temperature steam crosslinking and debinding integrated treatment: The obtained fiber filaments are placed in a honeycomb-type steam furnace. During the debinding and sintering process, water vapor is continuously introduced at a steam intake rate of 80L / h. The temperature is raised to 600℃ at a heating rate of 0.5℃ / min. The temperature is held at the target temperature of 600℃ for 1 hour, the steam intake is turned off, and then the temperature is lowered to room temperature to obtain inorganic fibers.

[0070] 4) Ceramization: Same as Example 1.

[0071] The obtained ceramicized fibers have an average diameter of 10 μm, an average tensile strength of 1.56 GPa, a YAG phase composition, and an average grain size of 23.4 nm.

[0072] SEM images of the fibers are attached. Figure 2 .

[0073] XRD patterns of fibers prepared at different temperatures are attached. Figure 3 As shown in the figure, the YAG fibers are essentially amorphous at 900℃, but diffraction peaks appear near 2θ = 33°. Comparing this to the standard YAG diffraction card (PDF#72-1315), these peaks are characteristic of YAG, indicating that a small amount of YAG crystalline phase has begun to form at 900℃. With increasing temperature, the intensity of the YAG characteristic peaks gradually increases, while the peak width narrows, indicating that the grain size of the YAG fibers gradually increases and the crystal structure becomes more complete. During the heating process, no intermediate phases YAP (YAlO3) or YAM (Y4Al2O9) are generated in the YAG fiber crystal phase, demonstrating that single-phase YAG fibers can be prepared using the polymer precursor method.

[0074] Example 4

[0075] Preparation of Yttrium Aluminum Oxide Continuous Ceramic Fibers

[0076] 1) Precursor synthesis: Aluminum isopropoxide and yttrium acetylacetonate were added to n-propanol, with the ratio of aluminum isopropoxide to yttrium acetylacetonate being equivalent to a molar ratio of Al to Y of 5:2. The mixture was stirred and refluxed at 90°C for 3 hours. Then, acetylacetonate was added at 80°C in a molar fraction equal to 0.6 times the total amount of aluminum isopropoxide and yttrium acetylacetonate, and the mixture was refluxed for 1.5 hours. A mixture of water and n-propanol with a mass ratio of 1:4 was then added dropwise at a rate of 1 drop / s, with the molar ratio of aluminum isopropoxide, yttrium acetylacetonate, and water being 1:0.6. The mixture was refluxed for 2 hours after the addition was complete. The mixture was then distilled at atmospheric pressure at 240°C for 4.5 hours, held at that temperature for 2 hours, and then cooled to room temperature to obtain the yttrium aluminum oxide ceramic precursor, which had a softening point of 120°C and a ceramic yield of 37.6%.

[0077] 2) Melt spinning: The yttrium aluminum oxide ceramic precursor with a softening point of 120℃ and a molar ratio of Al to Y of 5:2 is heated to 165℃. After it melts into a uniform melt and removes residual bubbles, melt spinning is carried out at 165℃. The filament outlet diameter is 0.2mm, the screw extrusion pressure is 20MPa, and the fiber is taken in at a rate of 35Hz to obtain the fiber precursor.

[0078] 3) High-temperature steam crosslinking and debinding integrated treatment: Same as Example 3;

[0079] 4) Ceramization: Same as Example 1.

[0080] The obtained ceramicized fibers have an average diameter of 10 μm, an average tensile strength of 0.98 GPa, a crystal phase composition of YAG phase and α-Al2O3 phase, and an average grain size of 72.8 nm.

[0081] Example 5

[0082] Preparation of Yttrium Aluminum Oxide Continuous Ceramic Fibers

[0083] 1) Precursor synthesis: Same as in Example 1;

[0084] 2) Melt spinning: Same as in Example 1;

[0085] 3) High-temperature steam crosslinking and debinding integrated treatment: Same as Example 3;

[0086] 4) Ceramization: Same as Example 3.

[0087] The obtained ceramicized fibers have an average diameter of 10 μm, an average tensile strength of 1.06 GPa, a crystal phase composition of YAG phase and α-Al2O3 phase, and an average grain size of 66.2 nm.

[0088] Example 6

[0089] Preparation of Yttrium Aluminum Oxide Continuous Ceramic Fibers

[0090] 1) Precursor synthesis: Same as in Example 2;

[0091] 2) Melt spinning: Same as in Example 2;

[0092] 3) High-temperature steam crosslinking and debinding integrated treatment: Same as Example 3;

[0093] 4) Ceramization: Same as Example 1.

[0094] The obtained ceramicized fibers have an average diameter of 10 μm, an average tensile strength of 1.27 GPa, a crystal phase composition of YAG phase and γ-Al2O3 phase, and an average grain size of 5.2 nm.

[0095] Example 7

[0096] Preparation of Yttrium Aluminum Oxide Continuous Ceramic Fibers

[0097] 1) Precursor synthesis: Aluminum isopropoxide and yttrium acetylacetonate were added to n-propanol, with the molar ratio of aluminum isopropoxide to yttrium acetylacetonate equivalent to Al:Y elements being 5:3.5. The mixture was stirred and refluxed at 90°C for 3 hours. Subsequently, 0.6 molar fractions of acetylacetonate were added to aluminum isopropoxide and yttrium acetylacetonate at 80°C, and the mixture was refluxed for 1.5 hours. Then, a mixture of water and n-propanol with a mass ratio of 1:4 was added dropwise at a rate of 1 drop / s, with the molar ratio of aluminum isopropoxide, yttrium acetylacetonate, and water being 1:0.6. The mixture was refluxed for 2 hours after the addition was complete. The mixture was then distilled at atmospheric pressure at 270°C for 3.5 hours, held at that temperature for 2 hours, and then cooled to room temperature to obtain the yttrium aluminum oxide ceramic precursor, with a softening point of 120°C and a ceramic yield of 39.4%.

[0098] 2) Melt spinning: The yttrium aluminum oxide ceramic precursor with a softening point of 120℃ and a molar ratio of Al to Y of 5:3.5 is heated to 165℃. After it melts into a uniform melt and removes residual bubbles, melt spinning is carried out at 165℃. The filament outlet diameter is 0.2mm, the screw extrusion pressure is 20MPa, and the fiber is taken in at a rate of 35Hz to obtain the fiber precursor.

[0099] 3) High-temperature steam crosslinking and debinding integrated treatment: Same as Example 3;

[0100] 4) Ceramization: Same as Example 1.

[0101] The obtained ceramicized fibers have an average diameter of 10 μm, an average tensile strength of 1.30 GPa, a crystal phase composition of YAG phase and YAM phase, and an average grain size of 43.1 nm.

[0102] Example 8

[0103] Preparation of Yttrium Aluminum Oxide Continuous Ceramic Fibers

[0104] 1) Aluminum isopropoxide and yttrium acetylacetonate were added to n-propanol, wherein the molar ratio of aluminum isopropoxide to yttrium acetylacetonate, converted to Al and Y elements, was 5:3. The mixture was stirred and refluxed at 90°C for 3 hours. Then, acetylacetonate was added at 80°C in a molar fraction equal to 0.6 times the total amount of aluminum isopropoxide and yttrium acetylacetonate, and the mixture was refluxed for 1.5 hours. A mixture of water and n-propanol with a mass ratio of 1:4 was then added dropwise at a dropping rate of 1 drop / s, wherein the molar ratio of aluminum isopropoxide, yttrium acetylacetonate, and water was 1:0.6. The mixture was refluxed for 2 hours after the addition was complete. The mixture was then distilled at atmospheric pressure at 260°C for 4 hours, held at that temperature for 2 hours, and then cooled to room temperature to obtain a yttrium aluminum oxide ceramic precursor with a softening point of 120°C and a ceramic yield of 38.7%.

[0105] 2) Melt spinning: A yttrium aluminum oxide ceramic precursor with a softening point of 120℃ and a molar ratio of Al to Y of 5:3 is heated to 165℃. After it melts into a uniform melt and removes residual bubbles, melt spinning is carried out at 165℃. The filament outlet diameter is 0.2mm, the screw extrusion pressure is 20MPa, and the fiber is taken in at a rate of 35Hz to obtain fiber filaments.

[0106] 3) High-temperature steam crosslinking and debinding integrated treatment: The obtained fiber filaments are placed in a honeycomb-type steam furnace. During the debinding and sintering process, water vapor is continuously introduced at a steam intake rate of 80L / h. The temperature is raised to 600℃ at a heating rate of 1℃ / min. The temperature is held at the target temperature of 600℃ for 1h. The steam intake is then turned off, and the temperature is lowered to room temperature to obtain inorganic fibers.

[0107] 4) Ceramization: Same as Example 1.

[0108] The obtained ceramicized fibers have an average diameter of 10 μm, an average tensile strength of 1.47 GPa, a YAG phase composition, and an average grain size of 23.4 nm.

[0109] Example 9

[0110] Preparation of Yttrium Aluminum Oxide Continuous Ceramic Fibers

[0111] 1) Precursor synthesis: Same as in Example 8;

[0112] 2) Melt spinning: Same as in Example 8;

[0113] 3) High-temperature steam crosslinking and debinding integrated treatment: The obtained fiber filaments are placed in a honeycomb-type steam furnace. During the debinding and sintering process, water vapor is continuously introduced at a steam intake rate of 80L / h. The temperature is raised to 600℃ at a heating rate of 2℃ / min. The temperature is held at the target temperature of 600℃ for 1 hour. The steam intake is then turned off, and the temperature is lowered to room temperature to obtain inorganic fibers.

[0114] 4) Ceramization: Same as Example 1.

[0115] The obtained ceramicized fibers have an average diameter of 10 μm, an average tensile strength of 1.34 GPa, a YAG phase composition, and an average grain size of 23.4 nm.

[0116] Compared to Examples 3, 8, and 9, the heating rate in the high-temperature steam crosslinking and debinding integrated treatment has no effect on crystal form or grain size, but it does affect tensile strength.

[0117] Example 10

[0118] Preparation of Yttrium Aluminum Oxide Continuous Ceramic Fibers

[0119] 1) Precursor synthesis: Same as in Example 8;

[0120] 2) Melt spinning: Same as in Example 8;

[0121] 3) High-temperature steam crosslinking and debinding integrated treatment: The obtained fiber filaments are placed in a honeycomb-type steam furnace. During the debinding and sintering process, water vapor is continuously introduced at a steam intake rate of 120L / h. The temperature is raised to 600℃ at a heating rate of 0.5℃ / min. The temperature is held at the target temperature of 600℃ for 1 hour. The steam intake is then turned off, and the temperature is lowered to room temperature to obtain inorganic fibers.

[0122] 4) Ceramization: Same as Example 1.

[0123] The obtained ceramicized fibers have an average diameter of 10 μm, an average tensile strength of 0.93 GPa, a YAG phase composition, and an average grain size of 23.4 nm.

[0124] Compared to Example 3, fibers can also be obtained with a steam intake of 120 L / h, but the average tensile strength decreases with the increase in steam intake.

[0125] Comparative Example 1

[0126] 1) Precursor synthesis: Aluminum isopropoxide and yttrium acetylacetonate were added to n-propanol, with the ratio of aluminum isopropoxide to yttrium acetylacetonate being equivalent to a molar ratio of Al to Y of 5:3. The mixture was stirred and refluxed at 90°C for 3 hours. Then, acetylacetonate was added at 80°C in a molar fraction equal to 0.6 times the total amount of aluminum isopropoxide and yttrium acetylacetonate, and the mixture was refluxed for 1.5 hours. A mixture of water and n-propanol with a mass ratio of 1:4 was then added dropwise at a rate of 1 drop / s, with the molar ratio of aluminum isopropoxide, yttrium acetylacetonate, and water being 1:0.6. The mixture was refluxed for 2 hours after the addition was complete. The mixture was then distilled at atmospheric pressure at 260°C for 4 hours, held at that temperature for 2 hours, and then cooled to room temperature to obtain the yttrium aluminum oxide ceramic precursor, which had a softening point of 120°C and a ceramic yield of 38.7%.

[0127] 2) Melt spinning: A yttrium aluminum oxide ceramic precursor with a softening point of 120℃ and a molar ratio of Al to Y of 5:3 is heated to 165℃. After it melts into a uniform melt and removes residual bubbles, melt spinning is carried out at 165℃. The filament outlet diameter is 0.2mm, the screw extrusion pressure is 20MPa, and the fiber is taken in at a rate of 35Hz to obtain fiber filaments.

[0128] 3) Steam crosslinking and desizing treatment: The obtained fiber filaments were placed in a constant temperature and humidity chamber, heated to 85℃, and held at 80% relative humidity for 60 min, then cooled to room temperature. Subsequently, the steam-crosslinked fibers were placed in a desizing and sintering integrated furnace for desizing to prepare inorganic fibers. The temperature was increased to 600℃ at a rate of 1℃ / min, held at the target temperature of 600℃ for 1 h, and then cooled to room temperature to obtain inorganic fibers.

[0129] The resulting inorganic fibers are black with a rough surface, are brittle and have no strength.

[0130] The TGA curves of the precursor in air atmosphere are attached. Figure 4 As shown in the figure, the weight loss of the YAG precursor from room temperature to 1350℃ can be divided into four stages. The weight loss rate from room temperature to 600℃ is approximately 50.6%, mainly due to the decomposition and removal of organic groups in the YAG precursor. The weight loss rate from 600℃ to 1050℃ is approximately 1%, and the weight loss curve tends to flatten out in this stage. The weight loss rate from 1050℃ to 1250℃ is approximately 9.7%, mainly due to the removal of residual carbon in the YAG precursor. The weight loss rate from 1250℃ to 1350℃ is 0%, and the weight loss curve is flat in this stage, indicating that the inorganicization process of the precursor is basically completed at 600℃. However, due to the high thermal decomposition temperature of yttrium acetylacetone contained in the YAG precursor, some residual carbon remains after 600℃, and the residual weight rate of the precursor at 1350℃ is 38.7%.

[0131] Comparative Example 2

[0132] 1) Precursor synthesis: Aluminum isopropoxide and yttrium acetylacetonate were added to n-propanol, with the molar ratio of aluminum isopropoxide to yttrium acetylacetonate equivalent to Al:Y elements being 5:2. The mixture was stirred and refluxed at 90°C for 3 hours. Subsequently, 0.6 molar fractions of acetylacetonate were added to aluminum isopropoxide and yttrium acetylacetonate at 80°C, and the mixture was refluxed for 1.5 hours. Then, a mixture of water and n-propanol with a mass ratio of 1:4 was added dropwise at a rate of 1 drop / s, with the molar ratio of aluminum isopropoxide, yttrium acetylacetonate, and water being 1:0.6. The mixture was refluxed for 2 hours after the addition was complete. The mixture was then distilled at atmospheric pressure at 240°C for 4.5 hours, held at that temperature for 2 hours, and then cooled to room temperature to obtain the yttrium aluminum oxide ceramic precursor, with a softening point of 120°C and a ceramic yield of 37.6%.

[0133] 2) Melt spinning: The yttrium aluminum oxide ceramic precursor with a softening point of 120℃ and a molar ratio of Al to Y of 5:2 is heated to 165℃. After it melts into a uniform melt and removes residual bubbles, melt spinning is carried out at 165℃. The filament outlet diameter is 0.2mm, the screw extrusion pressure is 20MPa, and the fiber is taken in at a rate of 35Hz to obtain the fiber precursor.

[0134] SEM images of the fiber precursor are attached. Figure 5 .

[0135] 3) Steam crosslinking and debinding treatment: Same as comparative example 1.

[0136] The resulting inorganic fibers are black with a rough surface, are brittle and have no strength.

[0137] Comparative Example 3

[0138] 1) Precursor synthesis: Aluminum isopropoxide and yttrium acetylacetonate were added to n-propanol, with the molar ratio of aluminum isopropoxide to yttrium acetylacetonate equivalent to Al:Y elements being 5:3.5. The mixture was stirred and refluxed at 90°C for 3 hours. Subsequently, 0.6 molar fractions of acetylacetonate were added to aluminum isopropoxide and yttrium acetylacetonate at 80°C, and the mixture was refluxed for 1.5 hours. Then, a mixture of water and n-propanol with a mass ratio of 1:4 was added dropwise at a rate of 1 drop / s, with the molar ratio of aluminum isopropoxide, yttrium acetylacetonate, and water being 1:0.6. The mixture was refluxed for 2 hours after the addition was complete. The mixture was then distilled at atmospheric pressure at 270°C for 3.5 hours, held at that temperature for 2 hours, and then cooled to room temperature to obtain the yttrium aluminum oxide ceramic precursor, with a softening point of 120°C and a ceramic yield of 39.4%.

[0139] 2) Melt spinning: The yttrium aluminum oxide ceramic precursor with a softening point of 120℃ and a molar ratio of Al to Y of 5:3.5 is heated to 165℃. After it melts into a uniform melt and removes residual bubbles, melt spinning is carried out at 165℃. The filament outlet diameter is 0.2mm, the screw extrusion pressure is 20MPa, and the fiber is taken in at a rate of 35Hz to obtain the fiber precursor.

[0140] 3) Steam crosslinking and debinding treatment: Same as comparative example 1.

[0141] The resulting inorganic fibers are black with a rough surface, are brittle and have no strength.

[0142] Comparative Example 4

[0143] 1) Precursor synthesis: Same as comparative example 1;

[0144] 2) Melt spinning: Same as Comparative Example 1;

[0145] 3) Steam crosslinking and debinding treatment: The obtained fiber filaments are placed in a honeycomb-type steam furnace. During the debinding and sintering process, water vapor is continuously introduced at a steam intake rate of 200L / h. The temperature is raised to 600℃ at a heating rate of 0.5℃ / min. The temperature is held at the target temperature of 600℃ for 1 hour. The steam intake is then turned off, and the temperature is lowered to room temperature to obtain inorganic fibers.

[0146] 4) Ceramization: Same as Example 1.

[0147] The resulting inorganic fibers were white, rough in surface, brittle, and lacked strength. This was likely due to excessive steam intake during the steam crosslinking and debinding processes, leading to a violent reaction during debinding and damaging the fiber structure.

[0148] The present invention has been described in detail above. Those skilled in the art will recognize that the invention can be practiced in a wide range of ways with equivalent parameters, concentrations, and conditions without departing from its spirit and scope, and without requiring unnecessary experiments. While specific embodiments have been provided, it should be understood that further modifications can be made to the invention. In summary, according to the principles of the invention, this application is intended to include any changes, uses, or improvements to the invention, including changes made using conventional techniques known in the art that depart from the scope disclosed herein.

Claims

1. A method for preparing continuous yttrium aluminum oxide ceramic fibers, comprising: 1) The yttrium aluminum oxide ceramic precursor is melt-spun to obtain fiber filaments; 2) The fiber filaments are subjected to steam crosslinking and degumming treatment or high-temperature steam crosslinking and degumming integrated treatment to obtain inorganic fibers; 3) The inorganic fibers are subjected to ceramization treatment to obtain the yttrium aluminum oxide continuous ceramic fibers; In step 1), the yttrium aluminum oxide ceramic precursor is prepared by the following method: An aluminum source and a yttrium source are added to a solvent, and the mixture is stirred and refluxed at a heating temperature of 60-110°C for 0.5-3 h. A complexing agent is added at a heating temperature of 60-90°C, and the mixture is refluxed for 0.5-2 h. A mixture of water and n-propanol with a mass ratio of 1 drop / s is then added dropwise, and the mixture is refluxed for 2 h after the addition is complete. The mixture is then distilled at a heating temperature of 180-270°C for 0.5-6 h, held at that temperature for 2 h, and then cooled to room temperature to obtain a yttrium aluminum oxide ceramic precursor. The amounts of aluminum source and yttrium source used, converted to the molar ratio of Al and Y elements, are 5:3.5-0.5; The aluminum source is aluminum isopropoxide; The yttrium source is yttrium acetylacetone; The solvent is n-propanol; The complexing agent is acetylacetone; The acetylacetone was 0.6 times the total molar fraction of aluminum isopropoxide and yttrium acetylacetone; The molar ratio of total aluminum source, yttrium source, and water is 1:0.6; In the melt spinning step, the softening point of the yttrium aluminum oxide ceramic precursor is 110-180℃; In step 2), when the molar ratio of Al and Y elements used in preparing the yttrium aluminum oxide ceramic precursor is less than 5:1, the fiber precursor is subjected to high-temperature steam crosslinking and debinding integrated treatment to obtain inorganic fiber. The operation of the high-temperature steam crosslinking and debinding integrated treatment is as follows: the fiber filament is placed in a honeycomb-type steam furnace, and water vapor is continuously introduced during the debinding and sintering process. The steam intake is 80-200 L / h, and the temperature is raised to 600℃ at a heating rate of 0.5-2℃ / min. The temperature is held at the target temperature of 600℃ for 1 h, the steam intake is turned off, and then the temperature is lowered to room temperature. In step 2), when the molar ratio of Al to Y elements used in preparing the yttrium aluminum oxide ceramic precursor is greater than or equal to 5:1, the fiber precursor is subjected to steam crosslinking and debinding treatment, or to the integrated high-temperature steam crosslinking and debinding treatment, to obtain inorganic fibers. The steam crosslinking and debinding process is as follows: the fiber filaments are placed in a constant temperature and humidity chamber, heated to 75-90℃, kept at 75-95% relative humidity for 0-60 min, cooled to room temperature, and then the fiber after steam crosslinking is placed in a debinding and sintering integrated furnace to debind and prepare inorganic fiber. The temperature is increased to 600℃ at 1℃ / min, kept at the target temperature of 600℃ for 1 h, and then cooled to room temperature.

2. The method according to claim 1, characterized in that: The melt spinning temperature is 20-60°C higher than the softening point of the precursor. In the melt spinning process, the diameter of the exit hole is 0.1-1 mm; The screw extrusion pressure is 5-30 MPa; The winding frequency is 15-40 Hz.

3. The method according to claim 1, characterized in that: In step 3) the ceramization step, the rate of temperature increase from room temperature to ceramization temperature is 10-30℃ / min; The ceramization temperature is 1100-1500℃; The ceramization time is 30 minutes to 2 hours; The atmosphere for ceramicization is air.

4. Continuous yttrium aluminum oxide ceramic fibers prepared by the method according to any one of claims 1-3; The yttrium aluminum oxide continuous ceramic fiber is composed of Al2O3 and Y2O3, and the molar ratio of Al to Y elements in the fiber is 5:3.5-0.5; The crystal phase composition of the yttrium aluminum oxide continuous ceramic fiber is: pure YAG phase or YAG phase mixed with... α -Al2O3、 γ -A mixture of at least one of Al2O3 and YAM phases; The yttrium aluminum oxide continuous ceramic fiber has an average diameter of 5-15 μm and a maximum tensile strength of 1.5 GPa.

5. The use of the yttrium aluminum oxide continuous ceramic fiber according to claim 4 in the preparation of a material having at least one of the properties of structural reinforcement and high-temperature insulation.

6. A material having at least one of the properties of structural reinforcement and high-temperature insulation, said material comprising the yttrium aluminum oxide continuous ceramic fiber as described in claim 4.

Citation Information

Patent Citations

  • A method for preparing yttrium aluminum garnet continuous fibers

    CN106927808B

  • Al-Si complex phase oxide continuous ceramic fiber and preparation method thereof

    CN111733484A